2003
DOI: 10.1046/j.1472-8206.2003.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic–pharmacodynamic study of apomorphine's effect on growth hormone secretion in healthy subjects

Abstract: Apomorphine (APO) stimulates growth hormone (GH) release via dopamine D2 receptors (DRD2). There is no specific study assessing the relationship between APO pharmacokinetic (PK) and the pharmacodynamic (PD) response e.g. GH release. The objective of the study is the PK-PD modelling of APO in healthy subjects. This is a randomized crossover study with s.c. administration of 5, 10, and 20 micro g/kg of APO in 18 healthy subjects. APO concentrations were modelled according to both a bi-compartmental model with ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
5
1
Order By: Relevance
“…Despite the fact that the ACT is a well-established paradigm for indirect assessment of sensitivity of postsynaptic DA D 2 receptors, one could argue that the results measured by the ACT only assess the functional state of the tuberoinfundibular system (Lal 1988;Aymard et al 2003). As changes in the tuberoinfundibular system do not represent a neurobiological basis of addictive behavior, the correlation of the GH response with severity of dependence and with nicotine exposure we found can hardly be explained by an isolated alteration of this system.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Despite the fact that the ACT is a well-established paradigm for indirect assessment of sensitivity of postsynaptic DA D 2 receptors, one could argue that the results measured by the ACT only assess the functional state of the tuberoinfundibular system (Lal 1988;Aymard et al 2003). As changes in the tuberoinfundibular system do not represent a neurobiological basis of addictive behavior, the correlation of the GH response with severity of dependence and with nicotine exposure we found can hardly be explained by an isolated alteration of this system.…”
Section: Discussioncontrasting
confidence: 66%
“…This might indicate a reduced sensitivity of central DA receptors due to smoking. Since the apomorphine-induced GH response is primarily mediated by DA D 2 receptors in the tuberoinfundibular system (Aymard et al 2003), this could be due to a reduced density or affinity of the DA D 2 receptors, or an altered signal transduction. Furthermore, the sensitivity of central DA D 2 receptors was inversely correlated with cotinine serum levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the single subject who experienced bradycardia and hypotension after 20 mg/kg subcutaneous apomorphine, and who responded to intravenous hydration, no serious adverse events were observed in response to apomorphine at the doses used in this study (10 to 20 mg/kg subcutaneous). Previous studies have reported minor side effects including somnolence, nausea, dizziness, and hallucinations in response to apomorphine (Aymard et al, 2003;Bowron, 2004;Menon and Stacy, 2007). To prevent apomorphine-induced nausea during the PET proto-col, we premedicated study participants with the antiemetic trimethobenzamide (Bowron, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the stimulation of GH secretion upon administration of the dopamine (DA) receptor agonist apomorphine (APO) is widely used to assess the functional state of the tuberoinfundibular system and of postsynaptic DA receptor (DR) function (Aymard et al, 2003). Apomorphine is an unselective DR agonist acting primarily at the postsynaptic DR D 2 receptor subtype, thereby directly stimulating GH release via pituitary DR D 2 receptors or indirectly by GHRH (Aymard et al, 2003). Several studies investigated APO‐induced GH secretion in alcoholic subjects after 2 or 3 months of abstinence and found that the GH response was reduced compared with healthy controls (e.g., Dettling et al, 1995).…”
mentioning
confidence: 99%